Pengolahan Se’i Sapi dengan Memanfaatkan Asap Cair Sekam Padi dan Pengaruhnya Terhadap Kadar Air, pH dan Organoleptik - Erixon Firanto Umbu Deta Lunggi; Yessy Tamu Ina (Universitas Kristen Wira Wacana Sumba, 2024)
This research aims to determine the effect of different concentrations of rice husk liquid smoke on water content, pH, fat content and organoleptics in beef se'i including (color, taste, texture and preference). The research material used in this research was 6 kg of beef. This research used a Completely Randomized Design (CRD), consisting of 4 treatments and 5 replications, namely P1=rice husk liquid smoke concentration 0.5%, P2=rice husk liquid smoke concentration 1%, P3=rice husk liquid smoke concentration 1.5 % and P4 = concentration of rice husk liquid smoke 2% so there are 20 sample units. The observation variables are water content, pH, fat content and organoleptics (color, taste, texture, preferences). The data is analyzed with a confidence level of 5%, if the results have a real effect then proceed with a real difference test. Organoleptic data were statistically processed using the Non-Parametric Kruskal Wallis method. The results of the research carried out can be concluded that smoking cow se'I with a high concentration of rice husk liquid smoke can increase the percentage of water content and pH and have an effect in increasing the panelists' acceptance of organoleptic se'I by obtaining a slightly brownish, soft and soft se'I color. distinctive taste.